Clay court tennis: men`s elite competitive performance analysis - Al Khalili Mohaned, M. E.; Stepanova, I. O.; Abitaev, A. V. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to determine factors affecting the tennis match scoring run as exemplified by two successive tennis plays on clay courts between the TOP-20 tennis players of the men's ATP rankings. Methods and structure of research. Based on the analysis of the literature data and observation of the tennis plays on clay courts at the level of TOP-20 men`s ATP rankings, 21 variables (indicators) of strategic actions were identified. Proceeding from the correlation analysis, out of 21 indicators, 15 ones were singled out as suitable for a factor analysis. They were subjected to a canonical factor analysis without axis rotation. As a result, we got 8 factors explaining almost 100% of variance of the game results. Results of the study. Almost 100% of the data changes are accounted for 8 factors, which include all the indicators of competitive performance in men's singles on clay courts at the level of TOP-20 ATP rankings. At this level, there are 7 indicators that are the most informative and convenient from the point of view of the competitive process management, as on other surfaces and in other categories. Conclusion. A further study the factors of competitive activity that affect the outcome of games is required: in women's games, on different surfaces, at different levels; tactical and technical indicators.